Study on PI3k gene expression in breast cancer samples and its association with clinical factors and patient survival - Lin, Jiang; Ding, Qi; Zhang, Guoying; Yin, Xiling (Cellular and Molecular Biology, 2022)
Breast cancer is the most common cancer among women in the world. The phosphatidylinositol 3-Kinase (PI3k), which regulates various cellular signaling pathways, is often elevated in human cancers. This study aimed to evaluate the expression of the PI3k gene in breast cancer. In this case-control study, 40 paraffin-embedded tissues of breast cancer and 40 adjacent non-tumor tissues were examined. After total RNA extraction and cDNA synthesis, the relative expression of the gene was obtained using the real-time-PCR method and evaluated by the 2-ΔΔCT method. Also, the association of gene expression with clinical factors and survival rate was investigated. Data analysis was performed by SPSS statistical software (version 22), t-test, and ANOVA. A p-value of less than 0.05 was considered significant. The results showed that PI3k expression was significantly increased in breast tumor tissues compared to non-tumor tissues (p = 0001). Consistent with these results, PI3k expression was associated with metastasis (p = 0.008) and high tumor grade (p = 0.01). In addition, increasing PI3k expression decreased overall survival compared to its low expression (p = 0.03). In general, PI3k plays a tumor-enhancing role in the progression of breast cancer. In addition, increased PI3k expression is associated with metastasis and poor prognosis of cancer, so that PI3k may be useful in the diagnosis, treatment, and prognosis of people with the disease. However, further investigation is needed to substantiate this claim.